Assessment of static loads on the locomotion system accompanying work on dairy stock farms (Journal of Medical Science, 2016)
The aim of this study was to perform statistical analyses of the load on the locomotion system during a variety of basic (elementary) work tasks associated with dairy cattle breeding, its causes and suggested key preventive measures illustrated, with an example of a large dairy stock farm. A comparative analysis was performed to compare the activities of the locomotion system during the use of traditional and modern milking methods. The analysis included elementary work tasks performed by 12 healthy, full-time stock workers (only males) employed at a large dairy stock farm in the Province of Wielkopolska, operating as a limited liability company. The working area consisted of two dairy cowsheds, in which different milking methods were used. OWAS (Ovako Working Posture Analysing System) method and the supporting WinOWAS computer system were employed to analyse all occupational activities generating static loads. The elementary work tasks in dairy cow breeding may involve significant loads on the musculoskeletal system. Unergonomic performance of these tasks results from bad habits and the level of mechanisation specific to a dairy cowshed. The proposed corrective and preventive measures presented in the analysis of specific works consists mainly in substituting the tools used so far with more ergonomic equipment, which is safer for the human locomotion system. The implementation of the proposed solutions requires specific investments; however, the risk of locomotor system disorders can be significantly reduced. Specific works, especially in traditional cowsheds, such as cow preparation for milking and the milking process itself, require prompt corrective measures, however, the lack of space may seriously limit the possibility to implement such measures, and stock workers are forced to assume awkward body positions. Education of stock farm staff should become one of the key preventive measures. Educational campaigns should be introduced within the framework of obligatory occupational safety training, in particular. However, the access to occupational safety training among individual farmers in Poland is currently very limited and may pose a challenge.